Evaluation of bone mineral density (BMD) and indicators of bone turnover in patients with hemophilia - Dagli, Mehmet (Bosn J Basic Med Sci, 2018)
A decrease in bone mass is observed in hemophilic patients. The aim of this study was to evaluate bone mineral density (BMD), parathyroid hormone (PTH), 25-hydroxy vitamin D (vitamin D), and a bone formation and resorption marker, procollagen type I N-terminal propeptide (PINP) and urinary N-terminal telopeptide (uNTX) respectively, in hemophilic patients and healthy controls. Laboratory parameters related to the pathogenesis of bone loss such as neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) were also evaluated. Thirty-five men over 18 years of age, with severe hemophilia (A and B) and receiving secondary prophylaxis, were included in the study. The same number of age-, sex-, and ethnicity-matched healthy controls were evaluated. Anthropometric, biochemical, and hormonal parameters were determined in both groups. No significant difference in anthropometric parameters was found between the two groups. The BMD was low in 34% of hemophilic patients. Vitamin D, calcium, and free testosterone levels were significantly lower (p < 0.001, p = 0.011, p < 0.001, respectively), while PTH, PINP, and activated partial thromboplastin time (aPTT) levels were significantly higher (p < 0.014, p = 0.043, p < 0.001, respectively), in hemophilic patients compared to controls. There was no significant difference between the two groups in NLR, PLR, phosphorus, thyroid-stimulating hormone, and uNTX level. The reduction of bone mass in hemophilic patients may be evaluated using the markers of bone formation and resorption, enabling early detection and timely treatment.